PROGRAM PENDUKUNG LAYANAN BIMBINGAN KONSELING DI SD/MI - Samriana; Saputri, Andi Aprilia; Elawati; Nengsih, Luluk Wahyu (Sindoro: Cendikia Pendidikan, 2024)
Guidance and Counseling (BK) services in primary schools play a crucial role in helping learners achieve their best potential. The complexity of learner development and the increasing demands of education demand the improvement of supporting programs for guidance and counseling services in primary schools. This study aims to understand the importance of the quality of counseling service programs, supporting programs for counseling services in primary schools, and improving facilities and infrastructure. Secondary data were obtained through a literature review study. Data collection techniques were carried out by literature study, namely studying related documents such as the plan for supporting counseling service programs in elementary schools and previous research. The results of this study are expected to help educators in running the counseling program better by understanding the importance of the quality of counseling service programs, supporting programs for counseling services in elementary schools, and improving facilities and infrastructure.